Structural and semantic features of verbs of interpersonal relations in Russian and Chinese - Li, Xiuyu (Litera, 2023)
The subject of the study is the structural and semantic features of verbs expressing interpersonal relationships in two different-structured Russian and Chinese languages. The purpose of the work is to provide a comparative description of the structure of verbs and their semantic features, as well as to identify the specifics of grammatical categories and compare the word-formation types of verbs in two languages. The following methods were used in this article: descriptive method, comparative method and component analysis method. From the point of view of the structural-semantic approach, the verbal vocabulary of the Russian and Chinese languages expressing interpersonal relations still remains insufficiently studied, so research in the field of verb semantics is relevant. The scientific novelty of the research consists in the fact that for the first time the common and unique features of the analyzed verbs are considered in comparison. It is shown that an important feature of Russian verbs is that they have many forms of word change with different meanings, whereas in Chinese the verb has no forms of word change and semantic diversity. The results of the research can be used in the process of teaching lecture courses on comparative lexicology of Russian and Chinese languages; when reading special courses in cognitive linguistics, linguoculturology, intercultural communication. The conclusion of this research is that compared with Russian verbs, which are characterized by a wealth and variety of affixes, Chinese verbs do not have possibilities of word formation for expressing different grammatical meanings. These various structural and semantic features of Russian and Chinese verbs complicate the understanding of the text and create significant difficulties in translation, as well as in the practice of teaching these languages as foreign.